CHARACTERISTICS AND NEEDS OF SLOW LEARNERS IN THE LEARNING PROCESS - Sesilya Karisma Dewi Ayu Hermawan; Suparmi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Inclusive education is a public school that facilitates students with disabilities, also known as children with special needs, where students have physical limitations, one example of which is slow learners. A slow learner is a learning disability where students face obstacles and difficulties in thinking. Slow learners can still follow the school curriculum, but they require slightly different treatment from regular students and additional time in the learning process. Before instruction begins, teachers must understand the characteristics and needs of children with special needs, particularly slow learners. This study aims to understand the characteristics and needs of slow learners in the learning process, as well as the strategies teachers can use in the learning process. The research method used is descriptive-qualitative, involving direct observation at SMP Negeri 22 Surakarta. By understanding the characteristics and needs of slow learners, teachers can adjust their teaching methods to suit the abilities of slow learners, thereby achieving good learning outcomes.